1991
DOI: 10.1038/nbt0991-844
|View full text |Cite
|
Sign up to set email alerts
|

Generation Of Transgenic Dairy Cattle Using ‘in vitro’ Embryo Production

Abstract: We have combined gene transfer, by microinjection, with 'in vitro' embryo production technology, enabling us to carry out non-surgical transfer, to recipient cows, of microinjected embryos that have been cultured from immature oocytes. Using this approach, we have established 21 pregnancies from which 19 calves were born. Southern blot analysis proved that in two cases the microinjected DNA had been integrated in the host genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1
11

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(122 citation statements)
references
References 23 publications
2
104
1
11
Order By: Relevance
“…Burdon and Wall [30] reported mosaic distribution of injected gene in mouse embryos. In cattle, the mosaicism was also reported in transgenic concepti [7] and bulls [30]. The study with bovine ealry embryos showed 80% of DNA-injected embryos were mosaic [35].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Burdon and Wall [30] reported mosaic distribution of injected gene in mouse embryos. In cattle, the mosaicism was also reported in transgenic concepti [7] and bulls [30]. The study with bovine ealry embryos showed 80% of DNA-injected embryos were mosaic [35].…”
Section: Discussionmentioning
confidence: 92%
“…We could not determine whether a fetus with the placenta was transgenic or not. If the embryo was mosaic, the fetus was possible to be non-transgenic, since Krimpenfort et al [7] obtained a mosaic transgenic conceptus, a non-transgenic fetus with a transgenic placenta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique is used to produce transgenic sheep and pigs (Hammer et al, 1985) and also transgenic cattle (Krimpenfort et al 1991). Using this technique earliest successful creation of transgenic mice was reported in 1980s (Gordon et al, 1980).…”
Section: Pronuclear Microinjectionmentioning
confidence: 99%
“…Optimisation of the method has been reached by preparing embryos by in vitro maturation of oocytes collected in the slaughterhouse, in vitro fertilization and in vitro development of the embryos after DNA microinjection until the blastocyst stage. This method does not imply the use of embryo donors and it considerably reduces the number of recipients [23].…”
Section: Gene Additionmentioning
confidence: 99%